Safety of interleukin inhibitors in patients with plaque psoriasis and history of neoplasms: a multicenter retrospective study – IL PSO (Italian landscape psoriasis) - Mario Valenti; Luciano Ibba; Sara Di Giulio; Luigi Gargiulo; Piergiorgio Malagoli; Anna Balato; Carlo G. Carrera; Paolo Dapavo; Eugenia V. Di Brizzi; Valentina Dini; Francesca Gaiani; Francesco Loconsole; et al. (Journal of Dermatological Treatment)
Background: Interleukin (IL) inhibitors are increasingly used in the management of moderate-to-severe plaque psoriasis. However, their use in patients with a history of cancer is debated.Objective: We conducted a multicenter retrospective study across nine Italian Dermatology Units to assess the real-world effectiveness and safety of IL inhibitors (IL-23, IL-17, IL-12/23) in 136 oncological patients with moderate-to-severe plaque psoriasis. In particular, we evaluated 116 patients who developed the neoplasm before starting the biologic with a mean time from diagnosis of neoplasia to the first biologic dose of 8.31 years. We also assessed 20 patients who received a diagnosis of neoplasm during treatment with IL inhibitors after a mean time of 2.41 years from the start of the biologic with a cumulative incidence of 3.06 per 1000 individuals.Results: Three patients experienced neoplasm recurrence during treatment with IL inhibitors, which led to the discontinuation of these drugs. In our study, biologics have demonstrated safety and effectiveness as treatment options for patients with both a history of neoplasm and those with concurrent tumors. However, further investigation is needed, particularly through larger and longer multicenter studies.